Exploring the Connection between Job Satisfaction and Different Forms of Organizational Commitment among Police - Nalla, Mahesh (Criminal justice and behavior, 2020)
Police operate around the world. Police organizations are tasked with a wide variety of duties, and successful police organizations need committed officers. The three main forms of organizational commitment are affective, normative, and continuance commitment. This study examined the relationship of overall job satisfaction and facet job satisfaction (transfers, pay, promotions, and supervision) on affective, normative, and continuance commitment among 550 officers working in the operations and investigation wings of the Lahore Police Stations in Punjab, Pakistan. Based on multivariate ordinary least squares (OLS) regression results, overall job satisfaction and facet satisfaction with transfers, pay, and supervision had significant positive effects on affective and normative commitment and negative associations with continuance commitment. Satisfaction with promotions, however, had a negative relationship with affective and normative commitment and a positive association with continuance commitment.